Implementation of the Maximum Increase Policy on the Sales Value of Taxable Object (NJOP) from the Perspective of Legal Certainty Based on Law Number 01 of 2022 Concerning the Financial Relationship Between the Central Government and Regional Governments - Gunawan, Verawati; Durahman, Dani; Haspada, Deny (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the implementation of the policy on the maximum limit of the increase in the Sales Value of Taxable Objects (NJOP) from the perspective of legal certainty with a specific focus based on Law Number 01 of 2022 concerning the Financial Relationship between the Central Government and Regional Governments (HKPD Law), with case study in Labuan Bajo, West Manggarai Regency. The background of this research arises from a drastic increase in NJOP, exceeding 100%, which has caused significant public concern and the potential for violations of the principles of justice and legal certainty. This study uses a normative juridical method with a descriptive qualitative approach. This research collects data through literature study, documentation, and interviews with government officials, tax law experts and affected citizens. The focus of the analysis is on legal certainty, regional government authority and legal protection for the public regarding the policy. The results show that the NJOP increase the policy in Labuan Bajo is not fully aligned with the principles of legal certainty. The absence of clear regulation on maximum limit of NJOP increase provides wide interpretive space for local governments (risking arbitrary decisions and weakened legal protection for taxpayers). This opens the potential for inequality, abuse of authority, and minimal legal protection for the public. Furthermore, the policy, which does not take into account the economic capacity of the community, has social implications such as anxiety, objections and potential legal conflict. The lack of public participation and insufficient dissemination of information further exacerbates social and economic distress among residents and local businesses. This study recommends revising regulations to provide explicit limits on NJOP increases by local governments (for the establishment of national standards and maximum thresholds for NJOP increases), as well as strengthening public objection mechanisms to be faster and more effective, and enhanced legal education and transparency within fiscal policy-making processes.